Ответ:
Пошаговое объяснение:
1 х - 3
-------- = ----------
х - 1 1 - х
1 * (1 - х) = (х - 3) * (х - 1)
1 - х = х² - х - 3х + 3
1 - х = х² - 4х + 3
1 - х - х² + 4х - 3 = 0
-х² + 3х - 2 = 0
D = 3² - 4 * (-1) * (-2) = 9 -8 = 1
- 3 - √1 -3 - 1
х₁ = -------------= --------- = 2
2 * (-1) - 2
- 3 + √1 - 3 + 1
х₂ = --------------- = ------------- = 1
2 * (-1) - 2
_______________________________________________
![\left \{ {{x-y=1} \atop {2x+3y=-8}} \right. \left \{ {{x-y=1} \atop {2x+3y=-8}} \right.](https://tex.z-dn.net/?f=%5Cleft%20%5C%7B%20%7B%7Bx-y%3D1%7D%20%5Catop%20%7B2x%2B3y%3D-8%7D%7D%20%5Cright.)
{ 3х - 3у = 3
{ 2х + 3у = - 8
3х + 2х = 5х
-3у + 3у = 0
3 + (-8) = 3 - 8 = -5
5х + 0 = - 5
5х = - 5
х = - 5 : 5
х = - 1
-1 - у = 1
у = - 1 - 1
у = - 2
- 2 * (- 1) = 2